Analysis of Factors Influencing Students’ Interest in Investing in the Capital Market in the D4 English Department, Faculty of Language and Literature, Universitas Negeri Makassar - Jefri, Riny; Kamariah, A.; Hajar, Andi; Novia, Lely (ARRUS Journal of Social Sciences and Humanities, 2025)
This study aims to examine knowledge on investments and minimum capital as factors influencing the investment interest of students in the D4 English Language Study Program. The research participants were active D4 English Language students in the odd semester of the 2025–2026 academic year, specifically cohorts 2023 to 2025. This study employed a quantitative approach using multiple linear regression analysis. The results showed that, both partially and simultaneously, knowledge on investment and minimum capital significantly affect the investment interest of D4 English Language students. Therefore, it can be concluded that investment knowledge and minimum capital currently have an influence on D4 English Language students.